Thyroid Storm Presenting As New-Onset Psychosis - Kriti Bhatia (MedEdPORTAL, 2014)
Abstract Introduction This simulation case provides an opportunity for emergency medicine residents and medical students to practice an often-repeated but practically overlooked teaching pearl: Always consider organic disease in patients presenting with functional symptoms. Methods The simulation case encompasses a patient who presents with psychiatric symptoms but has additional findings, mainly vital sign abnormalities that raise suspicion for another etiology. Specifically, he is in thyroid storm, which is a rare manifestation of severe thyrotoxicosis with a high potential for mortality. There are a wide array of presenting symptoms and vital sign abnormalities reflecting this life-threatening hypermetabolic state. Timely recognition and initiation of treatment are critical to patient outcome. Results Junior and senior emergency medicine residents who participated in the case cited it as a unique learning experience, emphasizing the principle of truly medically clearing a psychiatric patient by a thorough assessment and consideration of concerning pathologies. Discussion Based on the prompting needed by the instructor to help participants arrive at the diagnosis of thyroid storm, it is clear that this condition is not only rarely encountered in practice but also not readily considered. Given the associated high potential for mortality, the case serves as an important educational tool for emergency practitioners.